2018
DOI: 10.31274/archivalissues.11056
|View full text |Cite
|
Sign up to set email alerts
|

Digital Preservation Practices among Midwestern Four-year Public Colleges and Universities

Abstract: This article is the result of a study to survey the landscape of digital preservation practices and infrastructure at midwestern four-year public colleges and universities. It summarizes the staffing, tools, policy, and procedural characteristics of the survey population, compares these results to previous studies, and questions if a model for a successful program has emerged. The article concludes by arguing that instead of measuring digital preservation program development to existing ideal models, resource-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
2
7
1
Order By: Relevance
“…The plotting confirms that studies have been conducted covering institutions worldwide (Atkins et al, 2017;Bergau, 2010;Bergin, 2013;Engelhardt, 2013;Faria, 2017;Hedstrom and Montgomery, 1998;OCLC/RLGPREMIS Working Group, 2004;Sinclair et al, 2011). However, plotting of the studies also reveal that most of the studies come from North American region (Altman et al, 2013;Bellini et al, 2012;Bailey et al, 2014;Canadian Heritage Information Network, 2011;Gallinger et al, 2017;Gorzalski, 2018;Gregory, 2009;Kenney and Buckley, 2005;Li and Banach, 2011;Library and Archives Canada, 2010;Mantooth, 2009;McMillan et al, 2011;Reed, 2008;Thiede, 2017). Whereas some studies have also been conducted in other parts of the world including UK (McInnes and Phillips, 2009;Semple and Jones, 2006), New Zealand (Dorner, 2009), China (Jiazhen and Daoling, 2007;Mei et al, 2008) and Africa (Adu, 2016;Anyaoku et al, 2019;Kalusopa and Zulu, 2009;Kavishe, 2013;Masenya and Ngulube, 2019;Nworie, 2019;Olatokun, 2008).…”
Section: Literature Reviewsupporting
confidence: 58%
See 2 more Smart Citations
“…The plotting confirms that studies have been conducted covering institutions worldwide (Atkins et al, 2017;Bergau, 2010;Bergin, 2013;Engelhardt, 2013;Faria, 2017;Hedstrom and Montgomery, 1998;OCLC/RLGPREMIS Working Group, 2004;Sinclair et al, 2011). However, plotting of the studies also reveal that most of the studies come from North American region (Altman et al, 2013;Bellini et al, 2012;Bailey et al, 2014;Canadian Heritage Information Network, 2011;Gallinger et al, 2017;Gorzalski, 2018;Gregory, 2009;Kenney and Buckley, 2005;Li and Banach, 2011;Library and Archives Canada, 2010;Mantooth, 2009;McMillan et al, 2011;Reed, 2008;Thiede, 2017). Whereas some studies have also been conducted in other parts of the world including UK (McInnes and Phillips, 2009;Semple and Jones, 2006), New Zealand (Dorner, 2009), China (Jiazhen and Daoling, 2007;Mei et al, 2008) and Africa (Adu, 2016;Anyaoku et al, 2019;Kalusopa and Zulu, 2009;Kavishe, 2013;Masenya and Ngulube, 2019;Nworie, 2019;Olatokun, 2008).…”
Section: Literature Reviewsupporting
confidence: 58%
“…Bellini et al (2012) surveyed 103 associates of APARSEN in the USA and Europe and Digital preservation practices acknowledged that many of them were recording metadata for their d-contents by adhering to schemas like DublinCore (71%), self-developed schemas (36%), METS (33%), MODS (22%), MARCXML (21%), DDI (8%), DIDL (7%) and xMetaDiss (5%). Likewise, the study of Gorzalski (2018) in 54 institutions in the USA also affirmed that the majority (87%) were creating descriptive metadata, and structural metadata (41%). In the UK, Semple and Jones (2006) reported that less than one-third (30%) of the 90 Museum, Library and Archive Council (MLAC) members were adding metadata to their d-contents.…”
Section: Technical Practicesmentioning
confidence: 85%
See 1 more Smart Citation
“…However, in contrast some studies that covered worldwide organizations also pointed out toward lack of such policies (Bergin, 2013;Sinclair et al, 2011;UNESCO PERSIST, 2017). The studies that covered organizations in the North American region (mainly the USA and Canada) show satisfactory situation in terms of availability of related policies (Gorzalski, 2018;Japzon, 2008;Kenney and Buckley, 2005;Li and Banach, 2011;Library and Archives Canada, 2010). However, some studies identified a gap regarding the presence of such policies as well (Canadian Heritage Information Network (CHIN), 2011;Digital Preservation Policy Framework Taskforce, 2016;McMillan et al, 2011. It was astonishing to know that most of the studies conducted in organizations established in the European region identified a gap regarding the availability of digital preservation policies (Krimbacher et al, 2005;Lievesley and Jones, 1998;McInnes and Phillips, 2009;Semple and Jones, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…For metadata creation/capture only 10% had policies. Availability of policies (16%) and procedures (30%) for digital storage were available in only few of the institutions (Gorzalski, 2018). Majority (65.8%) of the 330 major university, national, general, and research libraries in 29 European countries lacked digital preservation policy.…”
Section: Resultsmentioning
confidence: 99%